EHRA expert consensus statement on arrhythmic mitral valve prolapse and mitral annular disjunction complex in collaboration with the ESC Council on valvular heart disease and the European Association of Cardiovascular Imaging endorsed cby the Heart Rhythm Society, by the Asia Pacific Heart Rhythm Society, and by the Latin American Heart Rhythm Society. Issue 12 (11th August 2022) - Sabbag, Avi; Essayagh, Benjamin; Barrera, Juan David Ramírez; Basso, Cristina; Berni, Ana; Cosyns, Bernard; Deharo, Jean-Claude; Deneke, Thomas; Di Biase, Luigi; Enriquez-Sarano, Maurice; Donal, Erwan; Imai, Katsuhiko; et al.
Graphical Abstract: Graphical Abstract Risk stratification scheme . Risk stratification aiming at assessing the risk of VAs and SCD in patients with MVP, involving two phases based on the clinical and imaging context and the uncovered arrhythmia. In the absence of ventricular tachycardia, phenotypic risk features will trigger the intensity of screening for arrhythmia. Green boxes indicate green heart consensus statements and yellow boxes indicate yellow heart consensus statements. High risk - sustained VT, polymorphic NSVT, fast (>180 bpm) NSVT, VT/NSVT resulting in syncope. ICD = implantable cardioverter defibrillator; LA = left atrium; LGE = late gadolinium enhancement; LV-EF = left ventricular ejection fraction; MAD = mitral annular disjunction; MV = mitral valve; PVCs = premature ventricular contractions; TWI = T-wave inversion; VT = ventricular tachycardia. #Additional ECG monitoring method may be used such as loop recorders.